2018
DOI: 10.1111/bor.12349
|View full text |Cite
|
Sign up to set email alerts
|

Late‐Quaternary history of ‘great lakes’ on the Tibetan Plateau and palaeoclimatic implications – A review

Abstract: Geomorphic evidence suggests that shorelines of 100–200 m above the modern lake levels were common across the Tibetan Plateau during late Marine Isotope Stage (MIS) 3. The timing of this lake‐level highstand is mainly based on radiocarbon ages. Problems surrounding the ages of lacustrine sediments at or beyond the limit of the radiocarbon‐dating method have created a need for alternative geochronometers. Chronological advances during the last decade have renewed interest in the timing of events beyond the limi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 92 publications
0
20
0
Order By: Relevance
“…2.6 Ma BP marked a period of increased variability of climate, lake level and extent, as well as changes in salinity (Huang et al, 1993;Wang et al, 2012;An et al, 2001;Heermance et al, 2013). The mega-lake system finally disappeared during the last 100 ka (Madsen et al, 2014;Yu et al, 2019). Today, only few saline lakes and playas exist, and the low-altitude parts of the basin are hyper-arid deserts (Chen and Bowler, 1986;Huang et al, 1993;Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…2.6 Ma BP marked a period of increased variability of climate, lake level and extent, as well as changes in salinity (Huang et al, 1993;Wang et al, 2012;An et al, 2001;Heermance et al, 2013). The mega-lake system finally disappeared during the last 100 ka (Madsen et al, 2014;Yu et al, 2019). Today, only few saline lakes and playas exist, and the low-altitude parts of the basin are hyper-arid deserts (Chen and Bowler, 1986;Huang et al, 1993;Wang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the evolution of lakes in the region on longer timescales, as well as the mechanisms responsible, is important for predicting future lake level variations and changes of regional water resources. As the most direct evidence of lake level changes, geomorphological evidence, including paleo-shorelines, wave-cut benches and littoral sediments deposited during high lake level stands, are widely used in Late Quaternary lake level and paleoclimatic reconstruction [3]. Numerous radiocarbon ages of paleoshorelines, high-stand lacustrine sediments, and cores that were drilled on lake shores were reported from the 1980s to 2000s.…”
mentioning
confidence: 99%
“…The results have revealed that radiocarbon dating underestimates sedimentary ages older than~30-40 ka and the GLP likely occurred during MIS 5 [5,6]. Yu et al [3] reviewed studies of the GLP and provided a comprehensive summary of the ages of high lake levels for 48 lakes in the TP, and concluded that the GLP was dated to MIS 5 rather than to MIS 3.…”
mentioning
confidence: 99%
See 2 more Smart Citations